MODEL PROBLEM BASED LEARNING BERBASIS LITERASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KEMANDIRIAN BELAJAR SISWA KELAS IV MI MUHAMMADIYAH KRAMAT KEMBARAN - Badarudin Badarudin; Arifin Muslim; Elly Hasan Sadeli (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This research is a dilator behind the low critical thinking ability and independent learning attitude of students in the learning process in grade IV SD/MI. The purpose of this study was to determine the improvement of critical thinking skills and learning independence of students who received learning with literacy-based and non-PBL PBL models. This study uses a quasi-experimental method with a Non equivalent [Pre-Test and Post-Test] Contro lGroups Design (NCGD) design. The experimental group was given treatment using a literacy-based PBL model while the control group learning took place in natural situations or in this study called non-PBL. The subjects of this study were 39 students of class IV MI Muhammadiyah Kramat, Kembaran District. The instruments used were critical thinking ability test sheets, student learning independence attitude questionnaires and learning observation sheets using the PBL model. The results of this study indicate that an increase in each stage in the implementation of PBL learning can facilitate the improvement of critical thinking skills and independent learning attitudes of fourth grade students of MI Muhammadiyah Kramat. There is an increase in critical thinking skills and independent learning attitudes between students who receive learning with literacy-based and non-PBL PBL models. The literacy-based PBL model further enhances students' critical thinking skills and independent learning attitudes compared to the non-PBL model.